Association of BMI and Sex With Moderate and Vigorous Physical Activity in Baltic Adolescents: Insights From the 2018 HBSC Study (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To examine the association of the overlap of body mass index (BMI) and sex with moderate (MPA) and vigorous (VPA) physical activity among adolescents in the Baltic Region.Methods: This study analysed data from the 2018 HBSC study, including 12,934 adolescents (mean age: 13.6 ± 1.6 years) from Estonia, Latvia, and Lithuania. MPA was self-reported and categorised as ≤6 dayS/week or 7 days/week, while VPA was classified as daily or non-daily. BMI was derived from self-reported height and weight and categorised into underweight, normal weight, overweight, or obese. Descriptive statistics were presented as relative frequencies with 95% confidence interval (CI).Results: Overall, 82.4% (95% CI = 81.6%–83.0%) of adolescents engaged in moderate physical activity